2017
DOI: 10.1097/md.0000000000006050
|View full text |Cite
|
Sign up to set email alerts
|

The association of ideal cardiovascular health and left ventricle hypertrophy in rural population of northeast China

Abstract: In 2010, the American Heart Association (AHA) published a new concept “ideal cardiovascular health” (CVH), which consisted of 4 behaviors (smoking, body mass index [BMI], physical activity, and diet score) and 3 health factors (total cholesterol [TC], blood pressure [BP], and fasting plasma glucose [FPG]). This study was aimed to investigate the association between CVH with left ventricle hypertrophy (LVH) in a rural general population.From January 2012 to August 2013, we conducted this cross-sectional study u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…By the end of October 2021, only one scientific paper was found in the database. The finding of a linear correlation between MHR and serum uric acid levels in this study is consistent with the results of Chen et al based on the Northeast China Rural Cardiovascular Health Study’s (NCRCHS) cross-sectional epidemiological survey [ 19 ]; the detailed design and rationale of NCRCHS have been fully described elsewhere [ 20 ]. After adjusting for confounders, the authors employed multivariate logistic regression to demonstrate the independent relationship between MHR and the prevalence of hyperuricemia.…”
Section: Discussionsupporting
confidence: 91%
“…By the end of October 2021, only one scientific paper was found in the database. The finding of a linear correlation between MHR and serum uric acid levels in this study is consistent with the results of Chen et al based on the Northeast China Rural Cardiovascular Health Study’s (NCRCHS) cross-sectional epidemiological survey [ 19 ]; the detailed design and rationale of NCRCHS have been fully described elsewhere [ 20 ]. After adjusting for confounders, the authors employed multivariate logistic regression to demonstrate the independent relationship between MHR and the prevalence of hyperuricemia.…”
Section: Discussionsupporting
confidence: 91%
“…The concept of ideal CVH appeared in 2010 in the core of the American Heart Association to improve the health of the USA population [19]. Since then numerous observational studies have demonstrated that a higher number of ideal LS7 components is associated with more favourable outcomes [20,25,27,28,[35][36][37][38]. In addition, ideal goals in CVH metrics have also been related with lower rates of PAD and subclinical atherosclerosis in multiple large cross-sectional and longitudinal observational studies in different populations [7,21,26,27,39,40], but in America or China only 0.1% of the population were found to have all 7 ideal goals in CVH metrics [41][42][43][44][45].…”
Section: Comparison With Previous Studies and Risk Factorsmentioning
confidence: 99%